Rise from the ashes! Resilience patterns in Patagonia pastoralist communities - Laborda, Luciana; Easdale, Marcos Horacio; Fallot, Abigail; Ocariz, María Paula; Tittonell, Pablo Adrian (Wiley, 2023)
Pastoral household resilience is shaped by the interplay between human agency and community resilience mechanisms. As a major component of pastoral household livelihoods, livestock can serve as an indicator to characterize resilience of pastoralist communities. In 2011, Patagonia faced droughts and a volcanic ashfall that affected livestock, water and forage resources during an ongoing economic recovery process. In two localities, we reconstructed the history of events that significantly influenced livestock dynamics over time at community and household levels. After the 2011 ashfall, herd sizes decreased variably by 13% to 91%. By 2019, only 37% of households recovered their herds. Although livestock dynamics were similar in both communities, households with small and medium-large herd sizes, high connectivity, off-farm income, and women involved in decision-making exhibited higher resilience. Understanding household diversity provided localized insights into community resilience (agency, adaptability).